2009
DOI: 10.1002/chp.20030
|View full text |Cite
|
Sign up to set email alerts
|

Online interprofessional health sciences education: From theory to practice

Abstract: Online learning (e-learning) has a nascent but established history. Its application to interprofessional education (IPE), however, is relatively new. Over the past 2 decades the Internet has been used increasingly to mediate education. We have come past the point of "should we use the Internet for education" to "how should we use the Internet for education." Research has begun on the optimal development of online learning environments to support IPE. Developing online IPE should follow best practices in e-lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Additionally, module developers attempted to integrate many innovative and engaging elements such as video clips of patient interactions, patient narratives, and progressive disclosure of patient histories using the patient's voice into the modules. Detailed reports on the design and unique features of individual modules are available elsewhere Hall et al 2009;Luke et al 2009, Solomon & Geddes 2009Solomon & Baptiste in press).…”
Section: Development and Implementation Of The Modulesmentioning
confidence: 99%
“…Additionally, module developers attempted to integrate many innovative and engaging elements such as video clips of patient interactions, patient narratives, and progressive disclosure of patient histories using the patient's voice into the modules. Detailed reports on the design and unique features of individual modules are available elsewhere Hall et al 2009;Luke et al 2009, Solomon & Geddes 2009Solomon & Baptiste in press).…”
Section: Development and Implementation Of The Modulesmentioning
confidence: 99%
“…As a result, IPE is increasingly being offered across health and social care sectors to an array of learners (pre-qualification, post qualification, continuing education) based in classrooms, simulation labs, clinical settings and increasingly through online (virtual) environments (e.g. Luke et al 2010;Bridges et al 2011;Palaganas et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Only professions that were involved in five or more reviewed studies are presented in Table IV. Carbonaro et al, 2008Chen, Klein, & Minor, 2009Clouder et al, 2011Connor, 2003Djukic et al, 2012Juntunen & Heikkinen, 2004Kinghorn, 2005Kovacich, 1996Luke et al, 2009Lund, Lam, & Parks, 2002Meyer et al, 2005Miers et al, 2007Richardson & Cooper, 2003Robinson, Hills, & Kelly, 2011Santy et al, 2009Schonfield & Spetman, 2007Skorga, 2002Solomon & King, 2010 Asynchronous discussions appeared as a technology-mediated instructional modality for IPE more often than any other in the reviewed studies Most studies reported positive outcomes at the reaction level (1) measured by questionnaires, surveys, focus groups, and interviews. Bendz et al (2001) hosted online discussions with students and learners, concluding that the online course was ''useful and very interesting,'' but that technical difficulties impeded the learning process.…”
Section: Level 1: Reactionmentioning
confidence: 91%
“…Included studies Summary of included study outcomes Posel et al, 2008Richardson & Cooper, 2003Skorga, 2002 Critical debate not commonly exchanged Used for one-way direct communication Little specific information collected on the impact on learning objectives Web-conferencing N Ā¼ 8 (13.3%) Synchronous multicasting of curriculum resources mediated through the internet not necessarily involving video, such as webinars Anderson & Friedemann, 2010Berg, Wong, & Vincent, 2010Carbonaro et al, 2008Chen et al, 2009Kinghorn, 2005Liu et al, 2004Meyer et al, 2005Robinson et al, 2011 Useful as a tool for rich two-way communication Satisfaction and post-activity selfrated skill assessments were typically positive In two cases, web-conference enabled observer ratings; learners were able to demonstrate learned skills in real time Multimedia video N Ā¼ 8 (13.3%) Asynchronous video media exchange Carbonaro et al, 2008Chen et al, 2009Luke et al, 2009MacDonald, Stodel, & Chambers, 2008Posel et al, 2008van Soeren, Devlin-Cop, Maude MacMillan, & Reeves, 2012 Videos frequently used to offer on-demand demonstration of clinical/collaboration skills In two cases, learners' session was videotaped to provide learners with feedback Some learner feedback indicated that in some cases access to video clips was problematic Video content enhanced interactivity and realism of curricula Instant messaging N Ā¼ 6 (10.0%) Synchronous text or other messaging delivered directly to learners in real time Lo et al, 2012Meyer et al, 2005Richardson & Cooper. 2003Robinson et al, 2011Skorga, 2002 Use of instant messaging often accompanied by other ICTs, with positive learner reaction Learners supported use of instant messaging where verbal contact is unnecessary or cumbersome More applicable to clinical settings Websites N Ā¼ 5 (8.3%) Websites providing on-demand access to curricular materials Bendz et al, 2001Brown et al, 2006DeBate et al, 2009Walsh & van Soeren, 2012 Studies often referred to web-based LMSs, with similarly positive feedback Web-based courses rated favorably on accessibility, readability and usefulness Websites...…”
Section: Ict Used Descriptionmentioning
confidence: 96%